A new explicit Runge-Kutta-Nystrom method with reduced phase-Lag and FSAL technique. - Senu, Norazak; Che, Thian Fung; Ismail, Fudziah (2012)
In this paper a new fourth~order explicit Runge-Kutta-Nystrom(RKN) method with dispersion of high order and FSAL technique for second-order systems of ODE with periodical solutions is introduced. The method has phase-lag order eight at a cost of three function evaluations per step or three effective stages. Numerical experiments show the relevance of the developed algorithm. It is found that the new method is more accurate than the current fourth-order (RKND and RKNH) methods developed by van der Bouwen and Sommeijer (1987) and Dormand (1996) respectively.